PENGARUH PEMBENAH TANAH TERHADAP PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS PADI PADA TANAH ASAL KARANGANYAR BERBASIS PUPUK ORGANIK BIO-SLURRY - Rhasita Sari Dewi; Sumarsono Sumarsono; Eny Fuskhah (Universitas Tribhuwana Tunggadewi, 2021)
The study aimed to compare the growth and production of rice between three varieties, namely Ciherang, IR 64 (Membrano), and Inpari 23 (Aromatic) without or with soil amendment application (dolomite) on andosol soil from Karanganyar. The research design used was a split-plot with a Completely Randomized Design. The main plot is treatment without soil amendment (R1) and with soil amendment (dolomite) (R2). Subplots were Ciherang (V1), IR 64 (V2), and Inpari 23 (V3) varieties. Parameters observed were plant height, number of panicles, panicle emergence age, crown weight, root weight, root crown ratio, strawweight, grain weight, 1000 grain weight, and harvest index. The results showed that the variety factor had a significant effect (P0,05) on the age of panicle emergence and the number of panicles. The age of panicle emergence and the best number of panicles was found in the IR 64 variety. Variety factors had no significant effect on plant height, crown weight, root portion weight, root canopy ratio, strawweight, grain weight, 1000 grain weight, and harvest index. Soil amendment factors have no significant effect on growth, biomass production, and rice production. It can be concluded that the most superior rice growth and production is IR 64 variety followed by Ciherang and Inpari 23 varieties.